Autonomic and cardiovascular responses on post-eccentric exercise recovery with blood flow restriction at different loads: Randomized controlled trial - Lemos, Leonardo Kesrouani [UNESP]; Teixeira Filho, Carlos Alberto Toledo [UNESP]; dos Santos, Fernanda Santana [UNESP]; Biral, Taíse Mendes [UNESP]; Cavina, Allysiê Priscilla de Souza [UNESP]; Pizzo Junior, Eduardo [UNESP]; Damasceno, Silas de Oliveira [UNESP]; Vendrame, Julia Waszczuk [UNESP]; Pastre, Carlos Marcelo [UNESP]; Vanderlei, Franciele Marques [UNESP] (Elsevier, 2022)
Introduction: Resistance training with blood flow restriction (BFR) has emerged as an method to gain strength and hypertrophy. However, the autonomic and cardiovascular repercussions of BFR and whether there is a dose-response relationship considering the load of the exercise when applied by means of eccentric contractions are not yet known. The objective was compare acute autonomic and cardiovascular responses following different loads of eccentric exercise with and without BFR. Methods: Sixty men were randomized into four groups: low and high load eccentric exercise (LLEE and HLEE); LLEE and HLEE with BFR (LLEE-BFR and HLEE-BFR). The participants underwent a single session of eccentric exercise for the quadriceps muscle in the dynamometer. Cardiovascular repercussions and heart rate variability were analyzed at baseline and for 60 min post-exercise. Variance analysis for a repeated measures model in the two-factor scheme was used with p<0.05. Results: There were no interactions (group vs. moments) for any of the cardiovascular variables and autonomic indices analyzed, and there were no differences between groups. Differences between moments were observed only for the respiratory rate variable in the LLEE-BFR and HLEE-BFR in the first minute of recovery (21.13±5.00 and 21.25±4.55 irpm, respectively) in relation to the baseline (17.07±2.81 and 18.00±2.92 irpm, respectively). Increase in vagal indices was observed in the final moments of recovery for the LLEE-BFR and HLEE-BFR. Conclusion: In conclusion, eccentric exercise with or without BFR with different load was not enough to cause autonomic and cardiovascular imbalance in post-exercise recovery. Clinicaltrials.gov - NCT03942510
Keywords: Autonomic nervous system; Cardiovascular system; Heart rate; Heart rate variability; Strength training; Vascular occlusion